(untitled) (Islas, 2026)
Introduction: Between 1927 and 1928, the Cuban cultural vanguard and its Latin American counterparts engaged in intense ideological debates sparked by the ambitions of a sector of Madrid’s intellectual circles to position themselves as a cultural meridian, as well as by the controversies that took place during the sessions of the VII Latin American Press Congress. These events have been scarcely addressed in Cuban historiography. Therefore, this study aims to analyze these debates, the stance adopted by the Cuban cultural vanguard, and the functioning of its intellectual networks. Methods: The methodological framework of intellectual history was employed, particularly its core categories: intellectuals and intellectual networks. To achieve the proposed objectives, journals associated with the cultural vanguard were analyzed, along with the newspapers Diario de la Marina and Heraldo de Cuba, as well as correspondence among key figures involved in these events. Results: The analysis of the reviewed materials not only made it possible to reconstruct the development of the ideological debates and the position adopted by the cultural vanguard, but also enabled the creation of a network diagram mapping intellectual connections during the period under study. Conclusions: The stance adopted by the Cuban cultural vanguard in both events was consistent with its search for a defining purpose, which led it to establish intellectual networks with its counterparts in a continuous exploration of new meanings for a Latin American integrative vocation, in opposition to hegemonic models of domination.